Evaluation of chitin as a biomarker of pathogenic fungal isolates - Ahmad Lafi, Ahmad Shehab; Jacinta Santhanam,; Tzar Mohd Nizam Khaithir,; Nur Fashya Musa,; Fahrul Huyop, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Chitin is a polysaccharide component of the inner cell wall of fungi that has been used to estimate fungal invasion in plant products. However, its detection in major pathogenic fungal species has not been investigated. The present study aimed to determine the chitin contents of pathogenic fungal species in order to evaluate its diagnostic potential as a biomarker for fungal infections. High performance liquid chromatography (HPLC) was used to measure chitin content. Pure chitin was acid hydrolyzed and the fluorescence of 9-fluorenylmethylchloroformate (FMOC-CI) derivatives of glucosamine produced were measured. The chitin contents of ten pathogenic fungal isolates were determined per mycelial dry weight. They varied from 18.61 (± 0.09) to 47.12 (± 0.50) µg/mg dry mycelial weight. Candida albicans and Cryptococcus neoformans exhibited the highest and lowest levels of chitin, respectively. Based upon relative amounts of chitin produced, three groups namely: high (Candida albicans, Cryptococcus gattii, Aspergillus niger and Penicillium at 47.12, 46.98, 46.05, and 44.15 µg/mg respectively), medium (Rhizopus, Aspergillus fumigatus, Fusarium solani, and Mucor at 36.61, 36.30, 35.03, and 34.84 µg/mg, respectively), and low (Candida tropicalis and Cryptococcus neoformans at 20.78 and 18.61 µg/mg, respectively), were identified. Chitin was not detectable in bacterial isolates used as controls. The chitin detection method offers a sensitive and specific tool for the quantification of chitin in pathogenic fungal isolates. The detection of chitin may be a useful assay for the diagnosis of fungal infections in clinical samples.